The Impact of Technological Innovation on the Future of Work - Maarten Goos; Melanie Arntz; Ulrich Zierahn; Terry Gregory; Stephanie Carretero Gomez; Ignacio Gonzalez Vazquez; Koen Jonkers (European Commission, Joint Research Centre (JRC), 2019)
New digital technologies more and more diffuse into the economy. Due to this digitisation, machines become increasingly able to perform tasks that previously only humans could to. Production processes and organizations are changing, new products, services and business models emerge. These trends have important implications for European labour markets. This working paper presents up-to date evidence on the consequences of technological innovations on labour markets based on the academic literature and discusses the resulting policy challenges along with examples of policy responses. One key finding is that so far recent technological change has had little effect on the aggregate number of jobs but leads to significant restructuring of jobs. This implies three key challenges for European labour markets: first, digitisation induces shifts in skill requirements, and workers' fate in changing labour markets crucially depends on their ability to keep up with the change. Secondly, digitisation is not a purely technological process, but requires an accompanying process of organisational change. Thirdly, digitisation comes along with rising shares of alternative work arrangements, due to more outsourcing, standardisation, fragmentation, and online platforms. These alternative work arrangements imply both new opportunities and challenges. These challenges require adequate policy responses at the European, national and regional level, which the working paper outlines for education and training policies, active labour market policies, income policies, tax systems and technology policies.
Keywords: 330; Technical Change; Structural Change; Labour Markets; Europe